One Font Doesn’t Fit All: The Influence of Digital Text Personalization on Comprehension in Child and Adolescent Readers - Shannon M. Sheppard; Susanne L. Nobles; Anton Palma; Sophie Kajfez; Marjorie Jordan; Kathy Crowley; Sofie Beier (Education Sciences, 2023)
Reading comprehension is an essential skill. It is unclear whether and to what degree typography and font personalization may impact reading comprehension in younger readers. With advancements in technology, it is now feasible to personalize digital reading formats in general technology tools, but this feature is not yet available for many educational tools. The current study aimed to investigate the effect of character width and inter-letter spacing on reading speed and comprehension. We enrolled 94 children (kindergarten–8th grade) and compared performance with six font variations on a word-level semantic decision task (Experiment 1) and a passage-level comprehension task (Experiment 2). Reading speed and comprehension were analyzed using generalized linear mixed-effects regression models. Independent samples t-tests compared speed and comprehension accuracy on personal best vs. worst font variation. A stability analysis was conducted to determine if participants had a stable personal best font variation within Experiment 1. The Experiment 1 stability analysis was statistically significant, and 58% of participants had a stable personal best font variation. Personal best font variations yielded significantly higher comprehension accuracy in both Experiments 1 and 2 and faster reading in Experiment 2. Using digital technology to personalize font may have important implications for school-aged readers.